2002
DOI: 10.1183/09031936.02.00274902
|View full text |Cite
|
Sign up to set email alerts
|

iNOS depletion completely diminishes reactive nitrogen-species formation after an allergic response

Abstract: Nitric oxide (NO) shows proinflammatory actions mainly via reactive nitrogen species (RNS) formation through superoxide-and peroxidase-dependent mechanisms. The purpose of this study was to examine the role of inducible NO synthase (iNOS) in RNS production, airway hyperresponsiveness, and inflammation after allergen challenge.Ovalbumin (OVA)-sensitised, iNOS-deficient and wild-type mice were used. RNS production was assessed by nitrotyrosine (NT) immunoreactivity in the airways. Airway inflammation and respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 31 publications
4
25
0
2
Order By: Relevance
“…Few inflammatory cells were observed in the lung of PBS-sensitized and challenged control mice. Lungs from OVA-sensitized and challenged mice showed severe inflammation, evidenced by epithelial damage and a large number of inflammatory cells infiltrated around the terminal bronchioles, alveolar sac and peripheral vasculature [17,18]. Luminal narrowing due to the airway wall oedema and luminal obstruction with excess mucus were also observed, which are typical hallmarks of bronchial inflammation.…”
Section: Reduction Of Oxidative Stress By Hpox Nanoparticles In the Pmentioning
confidence: 97%
“…Few inflammatory cells were observed in the lung of PBS-sensitized and challenged control mice. Lungs from OVA-sensitized and challenged mice showed severe inflammation, evidenced by epithelial damage and a large number of inflammatory cells infiltrated around the terminal bronchioles, alveolar sac and peripheral vasculature [17,18]. Luminal narrowing due to the airway wall oedema and luminal obstruction with excess mucus were also observed, which are typical hallmarks of bronchial inflammation.…”
Section: Reduction Of Oxidative Stress By Hpox Nanoparticles In the Pmentioning
confidence: 97%
“…Murine models have confirmed that iNOS expression is increased in airways following antigen challenge (28). To determine whether the increased inflammation observed following ADMA infusion was associated with altered iNOS expression in the airways, we visualized iNOS expression in lungs using immunohistochemistry (IHC) (Fig.…”
Section: Effect Of Elevated Adma On Inos Expression In Airway Epithelmentioning
confidence: 99%
“…Although it is known that NO plays a role in asthma by contributing to pulmonary inflammation after allergen challenge (49,69), the contribution of each of the NOS isoforms to inflammation in the airway is unclear. Pharmacological inhibitors of NOS have been used to study the role of specific NOS isoforms in asthma and have provided support for iNOSmediated NO production in the potentiation of airway inflammation (28,52). In contrast, overexpression of eNOS attenuates airway inflammation in a murine model of allergic asthma (60) indicating a delicate balance between NO production from constitutive NOS isoforms and that produced by iNOS.…”
mentioning
confidence: 99%
“…The literature shows that asthmatic airway hyperreactivity has to do with increased expression of iNOS (Koarai et al 2002;Schuiling et al 1998), which suggests that this isoform is involved in the pathogenesis AHR and asthma. We confirmed the role of iNOS in the present study, finding that after L-NAME pretreatment in healthy animals its expression was very low, but it dramatically increased after allergen exposition.…”
Section: Discussionmentioning
confidence: 98%